Generalized Linear Models - McCullagh, P. (Chapman and Hall/CRC Monographs on Statistics and Applied Probability., 2018)
The success of the first edition of Generalized Linear Models led to the updated Second Edition, which continues to provide a definitive unified, treatment of methods for the analysis of diverse types of data.